Saudi Arabia : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Saudi Arabia discusses that reforms are starting to yield positive results. Oil prices and production have been volatile, and uncertainties in the global oil market continue. Promoting non-oil growth and creating jobs for Saudi nationals remain key challenges. Non-oil growth is expected to strengthen further this year and over the medium term. Risks to the growth outlook are broadly balanced. The fiscal deficit declined in 2018; however, higher government spending has increased medium-term fiscal vulnerabilities to a decline in oil prices. Fiscal consolidation is needed to reduce these vulnerabilities. The fiscal framework should be further strengthened to help reduce the procyclicality of government spending. Reforms to improve the business environment are proceeding but need to be complemented by efforts to increase the cost competitiveness of Saudi labor. Government support to develop sectors of the economy should crowd in the private sector and be timebound and linked to performance.